Kepemimpinan Dan Kerjasama Tim Pada Mixue, Lubuk Begalung, Padang - Alifia aura syafira; Niken ardipa; Viona wijaya; Ririn afriani; Vivi nila sari (CV. ITTC INDONESIA, 2024)
Mixue, a brand known for its ice cream and tea drinks, has grown rapidly in the Asian market, especially in Indonesia. This research aims to analyze the factors that contribute to Mixue's popularity, the marketing strategies implemented, and the challenges faced in expanding its business. Data was obtained through consumer surveys, interviews with Mixue management, as well as analysis of social media and related literature. The research results show that Mixue's success is driven by a combination of affordable prices, product innovation, strategic location and effective digital marketing. However, challenges such as intense competition and changing consumer preferences remain major concerns. This study provides valuable insights for similar companies seeking to understand the dynamics of the ice cream and tea drinks market in Asia.